The role of TET-mediated DNA hydroxymethylation in prostate cancer. (15th February 2018) - Smeets, E.; Lynch, A.G.; Prekovic, S.; Van den Broeck, T.; Moris, L.; Helsen, C.; Joniau, S.; Claessens, F.; Massie, C.E.
Abstract: Ten-eleven translocation (TET) proteins are recently characterized dioxygenases that regulate demethylation by oxidizing 5-methylcytosine to 5-hydroxymethylcytosine and further derivatives. The recent finding that 5hmC is also a stable and independent epigenetic modification indicates that these proteins play an important role in diverse physiological and pathological processes such as neural and tumor development. Both the genomic distribution of (hydroxy)methylation and the expression and activity of TET proteins are dysregulated in a wide range of cancers including prostate cancer. Up to now it is still unknown how changes in TET and 5(h)mC profiles are related to the pathogenesis of prostate cancer. In this review, we explore recent advances in the current understanding of how TET expression and function are regulated in development and cancer. Furthermore, we look at the impact on 5hmC in prostate cancer and the potential underlying mechanisms. Finally, we tried to summarize the latest techniques for detecting and quantifying global and locus-specific 5hmC levels of genomic DNA. Highlights: Description of the link between prostate cancer and TET-mediated hydroxymethylation. Mapping of the hydroxymethylation landscape in prostate cancer. Overview of mechanisms influencing TET expression and activity in the prostate. Methods for detecting and quantifying global and locus-specific 5(h)mC levels.